Synthesis and Biological Profile of Substituted Azetidinyl Carboxamides, A Novel Class of Herbicidal Acyl-ACP Thioesterase Inhibitors - Bojack, Guido; Barber, David M.; Churchman, Luke R.; Dörnbrack, Christine; Lee, Stephanie; Payne, China M.; Posa, Luka; Reingruber, Anna M.; Schmutzler, Dirk; Frackenpohl, Jens (SynOpen, 2025)
Utilizing scaffold hopping and bioisosteric replacement strategies, we explored new azetidinyl carboxamide inhibitors of the plant-specific enzyme acyl-ACP thioesterase (FAT). Amongst the investigated compounds we identified new structural motifs that showed promising target affinity coupled with good in vivo efficacy against commercially important weed species. We further studied the structure-activity relationship (SAR) of the novel azetidinyl pyrazole carboxamide scaffold which showed promise as a new type of FAT inhibiting herbicides. Accordingly, a focused synthetic approach towards azetidinyl carboxamides was explored.
Keywords: herbicide; acyl-ACP thioesterase; azetidine; pyrazole carboxamide; structure-activity relationship; bioisosteres